Measurements of sediment oxygen demand (SOD)"in-situ" measuring chamber and its application for the stream water quality modeling and aquaculture management - Mohamed, Maketab (2003)
Sediment oxygen demand is defined as the rate of dissolved oxygen removal from the water column by the decomposition of organic materials in the bottom sediments. Accurate SOD rates are important, as they will allow for more precise permits specifications and therefore the degree or level of wastewater treatment needed. The “in situ" SOD chamber designed for the study was adapted from an earlier design by the USEPA (Hatcher, 1986). The chambers were used to measure the SOD levels in several rivers and streams. The results indicated a wide range of readings with high levels of SOD in river areas with high organic loadings. These measurements were used for the calibration and validation of a wasteload allocation water quality model. Another applied usage of the SOD chamber was for the management of aquaculture ponds. The knowledge of the SOD levels at the bottom of the aquaculture ponds will allow the management to schedule pond cleaning.